Peningkatan Kapasitas Pengelolaan Stres dan Ketrampilan Koping Petugas Panti Werda - Siti Nur Asiyah; Soffy Balgies (LP. Ma'arif Janggan Magetan, 2024)
Problems in the world of work, can be in the form of workloads that exceed capacity, conflicts with relationships, insufficient facilities, career delays and personal problems. This condition creates physical and psychological conditions in employees which is called work stress. The aims of this study are a) work stress problems faced by officers of the Tresna Werdha Service (PSTW) Technical Implementation Unit (PSTW) Pasuruan, b) increase the ability of UPT PSTW Pasuruan officers in dealing with work stress problems c) Reducing work stress experienced by UPT PSTW officers Pasuruan through stress management and coping skills. This study uses a participatory action research (PAR) approach by involving UPT PSTW Pasuruan officers and other stakeholders. The results showed that a) Work stress problems faced by UPT PSTW Pasuruan officers include human resources (HR), client and facility problems, b) There was an increase in the capacity of UPT PSTW Pasuruan officers in preparing stress management programs c) There was an increase in the capacity of UPT officers Pasuruan PSTW in doing coping skills